دراسة مقارنة لزمن وقت التعلم الاكاديمي في تعليم بعض المهارات الأساسية بكرة السلة والرماية المسدس الهوائي - الحميد, غصون ناطق عبد; ياور, فراس عجيل (Sulaimani Journal for Humanities, 2018)
The research aims to identify the academic time in the physical education lesson in the individual and differential games and compare the behavior of the teacher in the main section of the lesson in teaching some basic skills of basketball and shooting Air gun. The researchers used the descriptive method in the survey method to suit it and the nature of the research problem. Two for the individual game and another for the second game, for the second stage of the archery lesson and the second stage of basketball, the researchers were deliberately analyzed their behavior by the Anderson system. (12) minutes from the main section of (5) educational units according to the Anderson system, and then the researchers analyzed the behavior of (10) students in the basketball lesson and (10) students In the Shooting lesson, according to the Anderson system, when data was collected and processed by percentage tables and the number of observations for each, the two researchers concluded that the individual play teacher had the highest percentage of academic learning time from the class teacher, Is the teacher and the inability of students to master the movements, which requires direct intervention by the teacher, and recommend the researchers to increase the practice time and reduce the lost time lesson in learning the skills of basketball and make the teacher more effective during the lesson.